Repositioning therapeutic cancer vaccines in the dawning era of potent immune interventions. (October 2013) - Bot, Adrian; Marincola, Francesco; Smith, Kent A
Based on lessons learned with various immune interventions, this review aims to provide a constructive framework for repositioning therapeutic cancer vaccination. Intensive research throughout the past decade has identified key hurdles interfering with the efficacy of cancer vaccines. The vaccination concept still holds promise if positioned appropriately in minimal residual disease and select early disease stage cancer indications. However, in advanced cancer, it must be integrated with complementary immune interventions to ensure reconstruction of a functional immune repertoire and simultaneous blockade of immune inhibiting mechanisms. Vaccination could render complex and integrative immune interventions simpler, safer and more effective. The near future will witness an explosion of activities in the cancer immunotherapy arena, witnessing a rational repositioning of vaccines rather than their extinction.